Biogenesis and function of exosome lncRNAs and their role in female pathological pregnancy - Wang, Min; Zheng, Lianwen; Ma, Shuai; Lin, Ruixin; Li, Jiahui; Yang, Shuli (Frontiers in Endocrinology, 2023)
Preeclampsia, gestational diabetes mellitus, and recurrent spontaneous abortion are common maternal pregnancy complications that seriously endanger women's lives and health, and their occurrence is increasing year after year with a rejuvenation trend. In contrast to biomarkers found freely in tissues or body fluids, exosomes exist in a relatively independent environment and provide a higher level of stability. As backbone molecules, guidance molecules, and signaling molecules in the nucleus, lncRNAs can regulate gene expression. In the cytoplasm, lncRNAs can influence gene expression levels by modifying mRNA stability, acting as competitive endogenous RNAs to bind miRNAs, and so on. Exosomal lncRNAs can exist indefinitely and are important in intercellular communication and signal transduction. Changes in maternal serum exosome lncRNA expression can accurately and timely reflect the progression and regression of pregnancy-related diseases. The purpose of this paper is to provide a reference for clinical research on the pathogenesis, diagnosis, and treatment methods of pregnancy-related diseases by reviewing the role of exosome lncRNAs in female pathological pregnancy and related molecular mechanisms.